Tracing Antibacterial Compounds from Kaledang (Artocarpus lanceifolius Roxb.) Stem Bark - Hasan, Hamsidar; Tuloli, Tety; Bahri, Syamsul; Aman, La Ode (Pharmaceutical Sciences and Research, 2023)
Artocarpus lanceifolius Roxb. or kaledang is a species of the mulberry family, Moraceae. Several extracts from its family have been reported to have antibacterial activity. Thus, it is necessary to determine compounds that have nature as antibacterial to be raw materials for antibacterial herbal medicines. The purpose of the study was to trace compounds that have antibacterial activity from Artocarpus lanceifolius stem bark. The study method was extraction by graded maceration, fractionation with column vacuum chromatography (CVC), isolation by radial chromatography, determination of antibacterial activity by agar diffusion method using the Gram positive and Gram negative bacteria. The characterization result of antibacterial compounds from Artocarpus lanceifolius chloroform extract stem bark showed the presence of prenylated flavonoid compound, namely 14-hydroxyartonin E (previously reported) with a diameter of inhibition zone at 5% concentration was 14.5 ± 0.1 mm against S. aureus (medium category), and 16.20 ± 0.2 mm against S. mutans (strong category), 14.3 ± 0.2 mm against E. coli (medium category), and 16.8± 0.7 mm against P. aeruginosa (strong category). It is concluded that 14-hydroxyartonin E in Artocarpus lanceifolius showed potential antibacterial activity.